Treatment of posterior circulation non-saccular aneurysms with flow diverters: a single-center experience and review of 56 patients - Bhogal, Pervinder; Bäzner, Hansjörg (Journal of neuroInterventional surgery, 2017)
Background and purpose Non-saccular aneurysms of the posterior fossa are an uncommon pathology with no clear treatment strategy. The use of flow-diverting stents (FDS) has had mixed results. We sought to evaluate our experience of FDS for the treatment of this pathology. Methods We retrospectively reviewed our database of prospectively collected information for all patients treated only with flow diversion for an unruptured non-saccular aneurysm of the posterior circulation between February 2009 and April 2016. The aneurysms were classified as dolichoectasia, fusiform or transitional, and imaging characteristics including maximal diameter, disease vessel segment, MRI features (intra-aneurysmal thrombus, T1 hyperintensity in the aneurysmal wall, infarctions in the territory of the posterior circulation, and mass effect) were recorded alongside clinical and follow-up data. Results We identified 56 patients (45 men) with 58 aneurysms. The average age of the patients was 63.5 years. Twenty-two patients were symptomatic from the aneurysms at presentation. The majority of the lesions were vertebrobasilar in location (44.8%) with isolated vertebral lesions representing 29.3% of aneurysms. Transitional aneurysms were the most common (48.2%). The mean maximal diameter of the aneurysms was 11 mm. Angiographic exclusion of the aneurysms was seen in 57.4% of aneurysms with follow-up (n=47). During the follow-up period nine patients died. Conclusions Treatment of non-saccular aneurysms of the posterior fossa is technically possible. Early treatment, particularly of the fusiform and transitional subtypes, is recognized, as is treatment prior to the development of symptoms. A ‘watch and wait’ strategy with regular imaging follow-up could be employed for asymptomatic dolichoectasia.
Gesehen am 17.10.2018
Published online first 11 November 2016